1989
DOI: 10.1111/j.1748-1716.1989.tb08686.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of isotonic water transport in glands

Abstract: Since water and electrolytes pass cell membranes via separate channels, there can be no interactions in the membranes, and osmotic interactions between water and solutes can be expressed as the product of solute flux, frictional coefficient of solute, and length of pathway. It becomes clear that isotonic transport via a cell is impossible. In glands, where cation-selective junctions impede anion flux between the cells, isotonic water transport is only possible if sodium, after having passed the junction, is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…Full lines, the pathways for Na + and Cl-; dashed loops, the recycling paths for Na +. h I> Distance from the inside solution to the junction; h2 , distance from the junction to the outside bath Experimental evidence for this recycling of Na + [317] strongly supports this hypothesis. Furthermore, it is experimentally possible to vary the relative amounts of N a + and Cl-which pass through the glands.…”
Section: The Role Of Cellular Volume Regulation In Isotonic Water Trasupporting
confidence: 55%
See 2 more Smart Citations
“…Full lines, the pathways for Na + and Cl-; dashed loops, the recycling paths for Na +. h I> Distance from the inside solution to the junction; h2 , distance from the junction to the outside bath Experimental evidence for this recycling of Na + [317] strongly supports this hypothesis. Furthermore, it is experimentally possible to vary the relative amounts of N a + and Cl-which pass through the glands.…”
Section: The Role Of Cellular Volume Regulation In Isotonic Water Trasupporting
confidence: 55%
“…By a reformulation of Fick's law it is easily seen that the water/solute interactions can be expressed in terms of (a) forward and backward solute fluxes (b) free diffusion coefficients of the solutes, and (c) length of the transport path. An analysis in terms of this principle shows that isotonic water transport through a cell is impossible, even if the cell membranes were infinitely permeable to water [317]. The reason is that the friction of water against the stagnant solutes in the cell (for instance, proteins) forces the solvent (water) to lag behind the driving (transported) solute.…”
Section: The Role Of Cellular Volume Regulation In Isotonic Water Tramentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, as the relatively high osmotic permeability of some epithelial cell membranes became apparent,17 simple transcellular local osmosis was proposed as an explanation 17 ; however, theoretical treatments 18–20 eventually showed that local osmosis could produce only hypertonic but not isotonic fluid transport. This led to an alternative proposal based on electro-osmotic coupling of a recirculating electrolyte,20 but such a mechanism could not account for some experimental results 21. This review proposes a novel idea—epithelial layers that transport fluid might do so via a cell volume driven pulsatile mechanism that would be essentially a particular case of cell volume regulation.…”
Section: Fluid Transport In General and In The Corneal Endotheliummentioning
confidence: 99%
“…Изображения заимствованы из [3] и модифицированы Изменения объема могут быть задействованы также в процессе изоосмотического транспорта, при котором ýпителий сохраняет изоосмотич-ность транспортируемой жидкости по отноше-нию к внеклеточным растворам [7]. Объяснение данному явлению было предложено H. Ussing и K. Eskesen и заключалось в том, что регулируе-мый кругооборот активно выбрасываемого иона натрия контролирует тоничность транспортиру-емой жидкости [67]. Позже H. Ussing дополнил ýту гипотезу, объясняя изоосмотичность транс-портируемой жидкости следующим образом: «ре-циркулирование натрия регулируется осмоляр-ностью секетируемой жидкости за счет действия на объем клетки и, как следствие, на объем-чув-ствительные транспортеры и каналы натрия» [68].…”
unclassified